Perceived Health Beliefs of Fertile Age Women Upon Early Breast Examination - Aida Rahmatari (Jurnal Berkala Epidemiologi, 2014)
Breast cancer is still a problem in Indonesia, because 68.6% of patients go to the doctor at an advanced stage, while those who seek treatment at an early stage are only 22.4%. One of prevention that can be done is to detect early breast cancer by breast examination. This study was conducted to analyze the relationship between health beliefs felt by women of childbearing age with the act of checking their breasts early on. This research is an observational analytic study, which uses a case-control design. Samples were taken from the population by simple random sampling. The number of samples was 24 case groups and 24 control groups. The independent variable of research is perceived as perceived threats, perceived benefits, and perceived constraints. The dependent variable of the study was the act of checking the breast early on. The results of the study were then analyzed using the Chi-square test. The results of the bivariate analysis revealed that the variables related to the act of examining the breast early on were perceived threats (p = 0.013), and perceived obstacles (p = 0.021). Variables that are not related to the act of checking the breast early on are perceived benefits (p = 0.348). The conclusion that can be drawn is that the perceived threat and perceived obstacles that are felt by women of childbearing age are significantly related to the act of having a breast exam early. It is recommended for women to be able to be a savior for themselves as well as a motivator and motivator to fellow women in the surrounding environment to conduct early detection of breast cancer